ANALISIS KUALITAS PELAYANAN DENGAN MENGGUNAKAN METODE FUZZY-SERVQUAL PADA KANTOR POS PUSAT KOTA PADANG - Widia Afriyuni; Rahmiati Rahmiati; Muthia Roza Linda (Universitas Negeri Padang, 2019)
This study aims to analyze: (1) The level of customer satisfaction with the quality provided by the Padang City Center Post Office (2) Service attributes that need to be improved in service quality at the Padang City Center Post Office so as to improve customer satisfaction (3) Quality dimensions services that have the greatest influence on customer satisfaction at the Padang City Center Post Office. The population of this research is the Post Office customers with unknown number of respondents. The sampling technique of this study was accidental sampling technique with a total sample of 100 people. The data used is primary data. The data analysis technique uses the fuzzy-servqual method using Microsoft Excel software. The results showed that: (1) The level of consumer satisfaction is low because the overall servqual (gap) value is negative, namely -0.75 (2) There are 17 attributes that need to be improved from the 22 attributes that are tested to improve the quality of service at the Post Office Padang City Center (3) Dimensions of service quality with the biggest gap is the dimension of responsiveness with a value of -1.32.Keywords: Service Quality, fuzzy-servqual, customer satisfaction